Generalized Sum-Product Algorithm for Joint Channel Decoding and Physical-Layer Network Coding in Two-Way Relay Systems - Wübben, D; Yidong Lang (2010 IEEE Global Telecommunications Conference GLOBECOM 2010, 2010)
In this paper a physical-layer network coded two-way relay system applying Low-Density Parity-Check (LDPC) codes for error correction is considered, where two sources A and B desire to exchange information with each other by the help of a relay R. The critical process in such a system is the calculation of the network-coded transmit word at the relay on basis of the superimposed channel-coded words of the two sources. For this joint channel-decoding and network-encoding task a generalized Sum-Product Algorithm (SPA) is developed. This novel iterative decoding approach outperforms other recently proposed schemes as demonstrated by simulation results.